2006
DOI: 10.1007/s11096-006-9049-z
|View full text |Cite
|
Sign up to set email alerts
|

Customers’ expectations and satisfaction with a pharmacy not providing advanced cognitive services

Abstract: Customers reported a high level of satisfaction in a pharmacy where advanced cognitive services were not available. However, this should not discourage pharmacists from implementing APCS, because patients' expectations are based only on experiences with current distributive services, which fulfill their perceived needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 4 publications
4
30
0
Order By: Relevance
“…a convenience sample of those who had, or were experiencing a service were asked to evaluate the service in terms of satisfaction at that point of time [29,30,[32][33][34][35]. In studies reporting on satisfaction with intervention services, only one was randomised at pharmacy level [41] and one was randomised at patient level [40].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…a convenience sample of those who had, or were experiencing a service were asked to evaluate the service in terms of satisfaction at that point of time [29,30,[32][33][34][35]. In studies reporting on satisfaction with intervention services, only one was randomised at pharmacy level [41] and one was randomised at patient level [40].…”
Section: Methodsmentioning
confidence: 99%
“…Administration modes ranged from self completion on site [42,44,47,51], provider/researcher administered either on site (face to face interviews) [28,32], or via telephone [40,41,46], or mailed [30,34,39,43,45,[47][48][49][50]. One innovative study reported the use of trained volunteer patients as 'mystery shoppers' to assess and report their satisfaction with services provided by different health care professionals [36].…”
Section: Methods Of Satisfaction Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…However, on the contrary, many patients reported dissatisfaction about the information which they received. A new initiative of counselling has been taken by pharmacists in the management of chronic illness but patients still seems to be unfamiliar with the concept ( Van Geffen et al, 2009;Chewning and Schommer, 1996;Gastelurrutia et al, 2006). A review showed that the rates of counselling provided in pharmacies reported by consumers ranged from 8 to 56% (Puspitasari et al, 2009).…”
Section: Patient's Awareness Perception and Satisfaction Towards Coumentioning
confidence: 99%